The Costs of Store Sales for Retail Workers - van der Laken, Paul; Beijer, Susanne; Nijs, Sanne; van Veldhoven, Marc; Paauwe, Jaap (Frontiers in Psychology, 2020)
In the context of economic stagnation and recession, retailers face fierce competition and experience enormous pressure to increase their sales. In this study, we focus on the potential costs of higher store sales for retail workers by examining its effect on work engagement. Drawing on work intensification literature and the job demand-resources model, we study how job variety and workload, two job characteristics, mediate the relationship between store sales and engagement. Store revenue data and survey data of 525 sales employees, embedded in 110 stores of a large Dutch retail organization were used, to perform mixed models analyses. The analyses demonstrate that store sales is negatively related to job variety and positively related to workload. In turn, job variety positively affects work engagement while workload negatively affects work engagement. Based on multi-source, multilevel data it is thus shown that there are negative effects of store sales in retail. More insight is created into the job characteristics that explain the negative link between store sales and engagement. As it is empirically demonstrated that there are indeed costs associated with improved performance in retail, it is crucial that organizations ensure investments in maintaining resourceful work environments.